GAMBARAN FAKTOR-FAKTOR RESIKO PENULARAN PENYAKIT HIV-AIDS PADA LAKI-LAKI - Ratnawati Ratnawati; Herman Luawo; Zainudin Halid (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2020)
ABSTRACT Background: The epidemic of HIV-AIDS is a global crisis for development and social progress. The number of new cases of HIV in Indonesia tends to increase. The HIV-AIDS sufferers in Gorontalo Province in 2018 were 95. Based on gender, in Gorontalo Province in 2018, the number of men infected by HIV-AIDS is higher than women. Objective: The research was aimed at gaining a description of risk factors of the infection of HIV-AIDS on men in Gorontalo City. Methods: The research was analytical survey research employing a cross-sectional approach. The population is 30 people, and samples were 30 respondents determined by total sampling technique. The independent variable wa HIV-AIDS, and the dependent variable wa men with HIV-AIDS. Results:Findings revealed that the risk factors of sexual behavior included having sex (100%), anal sex and having multiple sexual partners (73.3%), same-sex relationship (66.7%), having sex multiple times and without using condom (50%), having sex with prostitutes (46.7%), and shemale (30%). Mostly men with HIV_AIDS and their partners suffered from sexually transmitted infections. The type of STIs mainly occurred was Gonorrhea (57%). The infection risk through parental was very low. Conclusion: is that the sexual behaviors were the main risk factors for HIV-AIDS infection in Gorontalo City. ABSTRAK Latar Belakang: Epidemi HIV-AIDS merupakan krisis global bagi pembangunan dan kemajuan sosial. Jumlah kasus baru HIV di Indonesia cenderung meningkat. Penderita HIV-AIDS di Provinsi Gorontalo pada tahun 2018 mencapai 95 kasus. Berdasarkan jenis kelamin, kasus HIV-AIDS di Provinsi Gorontalo pada tahun 2018 menyatakan laki-laki lebih tinggi dari perempuan. Tujuan : penelitian adalah mengetahui gambaran faktor-faktor resiko penularan penyakit HIV-AIDS pada laki-laki di Kota Gorontalo. Metode: Jenis Penelitian ini termasuk jenis penelitian survei analitik dengan pendekatan cross sectional. Populasi penelitian berjumlah 30 orang dan sampel berjumlah 30 orang dengan menggunakan teknik Total Sampling. Variabel independent adalah faktor resiko penularan penyakit HIV-AIDS dan veriabel dependent adalah laki-laki HIV-AIDS. Hasil penelitian: menunjukkan faktor resiko perilaku seksual meliputi pernah berhubungan seks (100%), seks anal & berganti-ganti pasangan (73.3%), seks sesama jenis (66.7%), seks lebih dari satu & tidak menggunakan kondom (50%), hubungan seksual dengan PSK (46.7%) dan Waria (30%). Resiko penularan melalui IMS sebagian dari laki-laki HIV-AIDS dan pasangannya pernah menderita IMS. Jenis IMS sebagian besar Gonorrhea (57%). Resiko penularan melalui parenteral sangat kecil. Kesimpulan: dari penelitian ini adalah faktor perilaku seksual merupakan faktor resiko utama penularan HIV-AIDS di Kota Gorontalo.